Transitioning from electrodialysis to reverse electrodialysis stack design for energy generation from high concentration salinity gradients. (15th September 2021) - Hulme, A.M.; Davey, C.J.; Tyrrel, S.; Pidou, M.; McAdam, E.J.
Highlights: Reverse electrodialysis stack design studied for large salinity gradients in recycle. Energy efficiency of a Reverse electrodialysis and Electrodialysis stack compared. Thicker electrodialysis membranes exhibited lower water permeance. Membrane properties and intermembrane distance critical for high concentrations. Abstract: In this study, stack design for high concentration gradient reverse electrodialysis operating in recycle is addressed. High concentration gradients introduce complex transport phenomena, which are exacerbated when recycling feeds; a strategy employed to improve system level energy efficiency. This unique challenge indicates that membrane properties and spacer thickness requirements may differ considerably from reverse electrodialysis for lower concentration gradients (e.g. seawater/river water), drawing closer parallels to electrodialysis stack design. Consequently, commercially available electrodialysis and reverse electrodialysis stack design was first compared for power generation from high concentration gradients. Higher gross power densities were identified for the reverse electrodialysis stack, due to the use of thinner membranes characterised by a higher permselectivity, which improved current. However, energy efficiency of the electrodialysis stack was twice that recorded for the reverse electrodialysis stack at low current densities, which was attributed to: (i) an increased residence time provided by the larger intermembrane distance, and (ii) reduced exergy losses of the electrodialysis membranes, which provided comparatively lower water permeance. Further in-depth investigation into membrane properties and spacer thickness identified that membranes characterised by an intermediate water permeability and ohmic resistance provided the highest power density and energy efficiency (Neosepta ACS/CMS), while wider intermembrane distances up to 0.3 mm improved energy efficiency. This study confirms that reverse electrodialysis stacks for high concentration gradients in recycle therefore demand design more comparable to electrodialysis stacks to drive energy efficiency, but when selecting membrane properties, the trade-off with permselectivity must also be considered to ensure economic viability.